AN EFFECT OF APPLICATION GOOGLE CLASSROOM IN LEARNING ENGLISH: A CASE STUDY IN ACCOUNTING STUDY PROGRAM AT MIND DEVELOPMENT UNIVERSITY - Fadly, Yossy; Efrizah, Doni; Purwanto, Dedi; Aulia, Yurika (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This research relates to the application of Google Classroom in learning English in the Accounting Study Program at Pembangunan Panca Budi University. The aim is to determine the effect of using Google Classroom in supporting Accounting learning. Respondents consisted of active students from class 2019, 2020, 2021 and 2022 who had used Google Classroom in semesters 1 and 2. The data collection method used was a research questionnaire whose data was analyzed using the SPSS program.The results of the research will later be published in the SINTA National Journal which has previously been presented at a national seminar, and for additional output a book/monograph with an ISBN will be published on the development of teaching models for courses in the Accounting study program.